The Representation of Hegemonic Masculinity in Louisa May Alcott’s Little Men: Life at Plumfield with Jo’s Boys - Achmad Fahreza Maghribbi Abu Bakar (Fakultas Ilmu Budaya, 2025)
This study examines the issue of masculinity as a form of gender stereotype in drama and classical novels. The purpose of this research is to uncover how masculinity is presented in novels and find the relationship with contextual conditions in people's social life and then find the author's critical position related to masculinity. This research is a qualitative research because it uses data in the form of text that cannot be measured through numbers. The data comes from the novel, the social life conditions of the author, the contextual conditions of the novel being written, and other sources that have been validated, namely: journals, articles, and official news pages. Hall's theory of representation is the main tool to uncover this research issue, supported by R.W. Connell's theory of masculinity to uncover the relationship of masculinity as a gender stereotype. It has been found that the data on the speech and masculinity behavior of the characters as gender stereotypes, which originate from and are influenced by the emotional conditions and social lives of the characters in the novel.
Dosen pembimbing Utama : Irana Astutiningsih, S.S., M.A., Dosen pembimbing Anggota : Nurhadianty Rahayu, M.A.,
Keywords: masculinity; gender stereotype; social life